Tanggung Jawab Hukum atas Kerugian yang Diderita Akibat Produk Cacat - Siti Balqis Alayya; Syifa Maura Adinda; Rani Bela Septia; Sintong Arion Hutapea (Lembaga Pengembangan Kinerja Dosen, 2025)
Consumer protection is a crucial aspect in the face of rapid economic development and increased industrial competition, including in the bottled water sector. The Aqua product packaging defect case in Semarang in July 2017 is a clear example of weak quality control and the importance of producer accountability. Defects such as bottle caps that can be pried off without breaking the seal create uncertainty over product safety and reduce consumer confidence. Law No. 8/1999 on Consumer Protection provides a strong legal basis for consumers to obtain safe products and claim compensation for losses due to defective products. Manufacturers have an absolute responsibility to ensure product safety through the implementation of strict quality control systems, early detection of physical defects, and digital tracking for product recalls if necessary. In addition, consumer education and optimization of public complaint media are important parts of the consumer protection system. With a comprehensive preventive and corrective approach, risks due to defective products can be minimized, and public trust in the industry can be maintained.